La Leucémie Lymphoïde Chronique dans la localité de Mostaganem. - Kerdagh, Fatima Zohra (My University, 2022)
Chronic lymphocytic leukemia (CLL) is characterized by blood and bone marrow infiltration, consisting of monoclonal populations of mature B lymphocytes. It is the most common form of leukemia. Rare before age 40, mostly seen in older people, more men than women. The present study aims to evaluate chronic lymphocytic leukemia from clinical data, assays of biological parameters and according to the Matute score and binet classification. In 25 patients with this disease, aged 36 to 83 years. In our study, a male predominance was observed in (64%) of the patients. Our results globally record positive blood group AB+ with a frequency of 48%. Finally, the study showed that the hereditary factor has no effect on chronic lymphocytic leukemia.
Keywords: chronic lymphocytic leukemia; male predominance; Matute score; binet classification